Committing to incentives: Should the decision to sanction be revealed or hidden? - Charlotte Klempt; Kerstin Pull (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Sanctions are widely used to promote compliance in principal-agent-relationships. While there is ample evidence confirming the predicted positive incentive effect of sanctions, it has also been shown that imposing sanctions may in fact reduce compliance by crowding-out intrinsic motivation. We add to the literature on the hidden costs of control by showing that these costs are restricted to situations where principals ex ante reveal their decision to sanction low compliance. If this decision is not revealed and agents do not know whether they will be sanctioned or not in case of low compliance, we do not find evidence of crowding-out - not even in those cases where agents firmly believe that they will be sanctioned in case of low performance.
Keywords: C72; C91; D03; 330; Intrinsic Motivation; Monetary Incentives; Job Performance; Leistungskontrolle; Leistungsanreiz; Normbefolgung; Leistungsmotivation; Agency Theory; Theorie